Analisis Penyesuaian Perpetaan RDTR Perkotaan Sebulu dengan Permen ATR/BPN No. 11 dan 14 Tahun 2021 - Savira Djumi Wardhani; Sandy, Aisyah Trees; Hotimah, Oot (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2025)
The issuance of Kutai Kartanegara Regional Regulation Number 7 of 2023 for the Spatial Plan (RTRW) of Kutai Kartanegara Regency for 2023-2042 forms the basis for preparing the RDTR for Sebulu Urban Area. The 2019 Kutai Kartanegara Regent Regulation guided the RDTR preparation using earlier regulations. New guidelines in 2021 necessitated RDTR mapping adjustments. This study aims to analyze RDTR mapping before and after improvements, using a qualitative approach and descriptive method. Techniques include overlay and topology analysis, evaluating strategic contents and the mapping database. Strategic content evaluation checks Green Open Space (RTH), forests, Sustainable Food Agricultural Land (LP2B), administrative boundaries, and national policies. Mapping database evaluation checks topology, database naming, attribute tables, element classification, geometry, and map presentation. Findings show RDTR mapping needed adjustments per Ministerial Regulations No. 11 and 14 of 2021, specifically RTH, LP2B, and spatial structure plans for hazardous materials. This research aims to guide improvements in Sebulu Urban Area's RDTR mapping.